Complementation analysis of mutants of nitric oxide synthase reveals that the active site requires two hemes. - Xie, Q W (1996)
For catalytic activity, nitric oxide synthases (NOSs) must be dimeric. Previous work revealed that the requirements for stable dimerization included binding of tetrahydrobiopterin (BH4), arginine, and heme. Here we asked what function is served by dimerization. We assessed the ability of individually inactive mutants of mouse inducible NOS (iNOS; NOS2), each deficient in binding a particular cofactor or cosubstrate, to complement each other by generating NO upon cotransfection into human epithelial cells. The ability of the mutants to homodimerize was gauged by gel filtration and/or PAGE under partially denaturing conditions, both followed by immunoblot. Their ability to heterodimerize was assessed by coimmunoprecipitation. Heterodimers that contained only one COOH-terminal hemimer and only one BH4-binding site could both form and function, even though the NADPH-, FAD-, and FMN-binding domains (in the COOH-terminal hemimer) and the BH4-binding sites (in the NH2-terminal hemimer) were contributed by opposite chains. Heterodimers that contained only one heme-binding site (Cys-194) could also form, either in cis or in trans to the nucleotide-binding domains. However, for NO production, both chains had to bind heme. Thus, NO production by iNOS requires dimerization because the active site requires two hemes.